Implementing the Humanistic Approach in 21st-Century Interactive Arabic Language Learning at Madrasah Ibtidaiyah - Yuni Lestari; Yusuf Muhtarom; Maksudin (Language, Technology, and Social Media, 2023)
The increasing demands of 21st-century education require language instruction models that not only enhance linguistic competence but also foster critical thinking, communication, collaboration, and creativity (4Cs). Arabic language learning in Indonesian madrasahs, however, continues to face challenges such as low student engagement, monotonous teaching practices, and limited integration of digital tools. This study aims to explore the implementation of the humanistic approach as an innovative framework for interactive Arabic language learning at Madrasah Ibtidaiyah. Employing a library research method, the study systematically reviewed books, peer-reviewed journals, encyclopedias, dictionaries, and electronic documents. The findings reveal that the humanistic approach promotes holistic student development by integrating cognitive, affective, and psychomotor aspects through supportive, interactive, and technology-mediated activities. It was also found that incorporating educational games and role-playing strategies enhances listening, speaking, reading, and writing skills, while simultaneously cultivating students’ confidence and motivation. This study contributes to the literature by positioning the humanistic approach as a relevant pedagogical model for addressing contemporary challenges in Arabic education. It highlights the need for teacher training, adaptive methodologies, and context-sensitive media to optimize learning outcomes. Future research should empirically test the long-term effectiveness of this approach across diverse educational settings.